DAMPAK URBANISASI TERHADAP PENINGKATAN KAWASAN KUMUH DI KOTA BANDUNG - Muhammad Rafi Fauzi; Mirna Nur Alia Abdullah (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2024)
Bandung city As one of the fastest growth economic became a target for urban people. Urban People are people that move from rural to a city. With the coming of urban people will make a new problem in housing sector that is slum area. Slum area are a crowded, unorganized place with low sanitation rate. Because these people can’t have a proper place to live they use the slum area as an alternative in this new urban life. Slum area can make more problem for the people live there, that problem van be from individual aspect or from the public. To prevent the making of slum area we have to bring all aspect from the public so they can participate to prevent slum area. This research aims to find out what the cause of the slum area and find solution for fixing the slum area. This research use qualitative method and literature reviews